Effect of flavolipid extracted from Chryseobacterium meningosepticum on serum lipid profile of Balb/C male mice(mus musculus) - Ghadar , Jafar (University of Thi-Qar Journal of Science, 2010)
The effect of flavolipid extracted from Chryseobacterium meningosepticum on the serum lipid profile of Balb/c male mice were investigated.The mice were randomaly divided into four groups(n=6), the first group was control treated with 0.9% NaCl ,while that other group were(I.P.) injected with 0.2mL of flavolipid extracted , the serum of second ,third and fourth groups were collected after 24 ,48and 72hrs respectively .from treated with flavolipid Serum total cholesterol,and triglyceride levels were low significantly in group(G2),compared with control group.while low density lipoprotein cholesterol decrease significantly in group G4 compared with control group.There was no significantly difference in high density lipoprotein cholesterol in the all treatd groups. LDL-C/HDL-C ratio was reduced significantly in all groups for injected with flavolipid compared with control group (p≤0.05).